The role of artificial intelligence in the production processes of radio electronic devices - Виноградська, В. Г. (ХНУРЕ, 2023)
The production of radio electronic devices is a complex process that involves several physical processes that must be optimized to ensure efficient and reliable device performance. In recent years, artificial intelligence (AI) has emerged as a powerful tool in optimizing these processes. By utilizing AI algorithms, designers and manufacturers can simulate, analyze, and optimize different aspects of device design and production, including electromagnetic simulations, quantum mechanics, statistical analysis, thermal management, and material selection. This article will explore the role of AI in the production processes of radio electronic devices and its impact on the industry